A desagregaç\~ao dos fluxos financeiros durante os eventos de parada súbita na entrada de capital externo - Marcos Antonio C. da Silveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The balance of payments' financial account aggregates a very heterogeneous set of capital flows. Among other features, these investments differ in terms of maturity, risk, liquidity and receptor. From this viewpoint, this paper analyzes comparatively the behavior of the main components of the financial account during the events of sudden stops in the net inflow of foreign capital to the emergent and developed countries. These events are identified in the literature as sharp and unexpected falls in the financial account surplus of a country as a result of the foreign investors' decisions to stop the financial flows to this country. The article concludes that these events are almost entirely explained by contraction of flows of portfolio investment flows and loans, whose average maturities are lower than that of the direct investment. In addition, investments in fixed income and for the public sector are relatively more stable than investments in variable income and for banks and private companies.
Keywords: F21; F32; 330; external capital flow; sudden stop; Kapitalmobilität